Risk Management Committee Characteristics’ Effects on Listed Companies’ Earnings Quality - EFENYUMI, Peter Mario Efesiri (The Journal of Accounting and Management, 2022)
This study evaluates how the characteristics of RMC (independence and diligence) impacts on listed companies’ earnings quality with 70 firms for ten year (2012-2021) using a comprehensive earnings quality model. It emphasizes the necessity of creating a separate and stand-alone subcommittee aside from the board entrusted with the responsibility for the setting and implementing firm’s risk overall policies including appetite and limit. According to the OLS analysis used to analyse the hypothesis, RMC characteristics have no appreciable impact on the listed firms’ profitability reporting. Conclusively, The absence or near absence of effective risk policy, planning and determination of company’s risk appetite and tolerance, regular performance of risk assessment and monitoring is detrimental to the growth and survival of firms and can lead to poor staff remuneration, unemployment, loss investments by investors in case of corporate failure resulting from board’s blindness to opportunities and rewards; and recommends that Management of companies and/or regulatory bodies should lay emphasis on the kind of people that make risk committee as it relates to earnings quality and continue to maintain reasonable standards in line with the current practices of companies within the sector.